Clinical and Electroencephalographic Features of the Seizures in Neuronal Surface Antibody-Associated Autoimmune Encephalitis - Wang, Yan; Yu, Yi; Hu, Yaping; Li, Ying; Song, Fan; Wang, Ying (Frontiers in Neurology, 2020)
Objectives: To investigate clinical and electroencephalographic features of the seizures in different types of neuronal surface antibody (NSAb)-associated autoimmune encephalitis (AE). Methods: The clinical data of the seizures were analyzed in 18 patients with NSAb-associated AEs diagnosed in the First Affiliated Hospital of Dalian Medical University. Results: From May 2013 to April 2019, a total of 18 cases of NSAb-associated AE were diagnosed, including 9 cases of leucine-rich glioma-inactivated 1 protein (LGI1) antibody-associated encephalitis, 7 cases of anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis, and 2 cases of anti-γ-aminobutyric acid B receptor (GABABR) encephalitis. All nine cases (100%) with LGI1 AE had seizures manifesting in three types: faciobranchial dystonia seizure (FBDS) (44.4%), mesial temporal lobe epilepsy (MTLE)-like seizure (66.7%), and focal to bilateral tonic–clonic seizure (FBTCS) (77.8%). Six of nine (66.7%) showed abnormal signal on hippocampus or basal ganglia in brain MRI. Five of seven cases (71%) with anti-NMDAR encephalitis had seizures manifesting in three types: focal aware seizure (40%), focal-impaired awareness seizure (20%), generalized tonic–clonic seizure (GTCS) (100%), and status epilepticus (SE) (40%). Three of seven (42.8%) showed abnormalities in brain MRI. Both patients with anti-GABABR encephalitis had seizures manifesting in two types: GTCS and MTLE-like seizure, one with SE. One showed abnormal signal on left hippocampus in brain MRI. All patients (100%) with three types of AE had abnormalities in electroencephalogram (EEG), showing diffuse (4/18) or focal slow waves (14/18) in background, interictal (10/18), or ictal (6/18) epileptic discharges in the temporal or other regions; two patients with anti-NMDAR encephalitis showed delta activity or rhythm in frontotemporal region. All patients with seizures showed good response to immunotherapy except one with LGI1 AE. Conclusions: Most patients with NSAb-associated AE had seizures; seizure types varied between different types of AE. In LGI1 AE, the hippocampus and basal ganglia were two main targets; the corresponding seizure type was MTLE-like seizure and FBDS, respectively. Anti-NMDAR encephalitis had more generalized than focal seizures. Delta activity or rhythm in the frontotemporal region in EEG was helpful for diagnosis. Anti-GABABR encephalitis was characterized by refractory seizures as initial symptom, mainly GTCS or MTLE-like seizure. Most seizures in NSAb-associated AE showed good response to immunotherapy, and antiepileptic drugs should be considered as an add-on symptomatic treatment.